Procedures in Teaching Listening without Using Language Laboratory in A State Senior High School of Mojokerto (RETAIN, 2018)
Abstrak Listening menjadi kegiatan yang lebih penting dan menantang bagi peserta didik dalam komunikasi sehari-hari dan proses pendidikan. Untuk membuat siswa mendapatkan pemahaman yang lebih baik dalam praktek bahasa, seorang guru haruslah mengatur dan menyajikan langkah-langakah yang tepat, aktifitas, media, materi, teknik, atau metode yang sesuai dalam proses pembelajaran. Pada proses belajar dan mengajar, sumber belajar memainkan peran penting pada proses pembelajaran bahasa. Laboratorium dan ruang kelas adalah contoh dari sumber belajar dalam jenis lingkungan. Meski begitu, sebenarnya masih banyak sekolah di Indonesia yang tidak memberikan standar kualitas laboratorium bahasa yang baik. Terkait dengan situasi diatas, peneliti tertarik untuk mengetahui dan mengamati secara mendalam prosedur dalam pengajaran listening tanpa menggunakan laboratorium bahasa di sebuah SMA Neger Mojokerto. Penelitian ini bertujuan untuk menjelaskan (1) hasil dari proses belajar dan mengajar listening tanpa menggunakan laboratorium bahasa (2) respon siswa pada pembelajaran listening tanpa menggunakan laboratorium bahasa. Penelitian ini dirancang sebagai penelitian studi kasus yang menggunakan analisis kualitatif. Objek penelitian ini melibatkan 38 siswa dan salah satu guru bahasa Inggris. Untuk mengumpulkan data, instrumen yang digunakan adalah observasi dan wawancara. Data kualitatif berupa catatan lapangan dan transkrip wawancara. Studi ini menemukan bahwa guru menggunakan langkah-langkah yang hampir serupa, meski tidak dalam urutan yang tepat dalam setiap pertemuan. Ini juga menunjukkan bahwasannya guru mengikuti pola saat mengajara listening. Pelaksanaan kegiatan belajar mengajar listening dan rencana pembelajaran terkadang dapat direvisi tergantung pada situasi kelas, sumber belajar yang sesuai, tersedianya media pembelajaran, beragam tugas dari listening, teknik, metode dan lain-lain. Berdasarkan hasil dari observasi dan wawancara, respon siswa terhadap pembelajaran listening dapat dikategorikan dalam respon positif dan respon negative. Kata Kunci: Listening, Mengajar Listening, Respon siswa Abstract Listening is becoming more important and a challenging activity for the learners in daily communication and the educational process. In order to make the students get a better understanding in their language practice, the teacher have to arranged and present appropriate procedures, suitable activities, the suitable media, materials, techniques, or the method of teaching-learning process. In the teaching-learning process, the learning resource plays the significant role in the language learning. The laboratory and classroom are the examples of learning resources in types of environment. Nevertheless, in fact, there are still many schools in Indonesia which do not provide a good standard quality of language laboratory. Related to this situation above, the researcher interested in knowing and deeply observing the procedures in teaching listening without using language laboratory in a state senior high school of Mojokerto. This study aimed to explain (1) the result of teaching-learning process of listening without using language laboratory (2) the students respond to learning listening without using language laboratory. This study was designed as case study research which employed qualitative analysis. The object of the study was involved 38 students andone of English teacher. In this study, the data were obtained from the observation and interview. Moreover, to collect the data, the researcher used some instruments in this study. The instruments of this study were in the form of field notes and the interview transcripts. This study found out that the teacher used steps were almost similar, even though did not in proper sequence in each meeting. It also indicates that the teacher follows a pattern when teaching listening. The implementation of teaching-learning activities of listening and the lesson plan sometimes can be revised depending on the class situations, suitable learning resources, available the learning media, varied listening task, technique, method and etc. In addition, based on the observation result and the interview result, the students respond towards the teaching-learning listening can be categorized in the positive and negative response. Keywords: Listening, Teaching Listening, Students Response.